Pengaruh Penggunaan Clickbait pada Judul Berita di Ayobandung.com Terhadap Minat Baca Mahasiswa Fakultas Ilmu Sosial dan Politik Universitas Bhayangkara Surabaya - Kautsar Senja; Julyanto Ekantoro; Ratna Setyarahajoe (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Reading interest is a strong desire of an individual to read a literature provided by the author with self-awareness, so that an individual will be encouraged to read and explore the contents of the literature without coercion. Student reading interest in a literature or current news is influenced by several factors, such as clickbait. This study aims to determine the impact of clickbait on the reading interest of students of the Faculty of Social and Political Sciences, Bhayangkara University, Surabaya on the ayobandug.com platform. This research is based on the discovery of a phenomenon found by the author on the ayobandung.com platform which has the characteristics of clickbait, where the title is found to be very interesting, but sometimes the content of the news does not match the content of the title raised. The population in this study were students of the Faculty of Social and Political Sciences, Bhayangkara University, Surabaya. The sampling technique in this study used a purposive sampling technique which has predetermined respondent criteria of 100 respondents. The data collection method was based on the survey method and the analysis technique in this study used the structural equation modeling method and used an analysis tool in the form of Partial Least Square (PLS). The research results found that the better the use of clickbait in the online media news titles ayobandung.com, the more it increases students' interest in reading.